THE AMERICA’S CHRONICALLY GAP SKIN-COLORS, THE BOURGEOUIS, AND THE BEE’S TENSION AS DISCOVERED IN AKEELAH: THE LOGO-THERAPHY APPROACH - Andra Fakhrian (EduLite: Journal of English Education, Literature and Culture, 2016)
Akeelah, a black American teenager, who faces many obstacles to achieveher purpose, to win the bee. Jibes, less attention from her mother, family,and even the roughness words are often heard by her until she becomesuncivilized. In the other side, Dylan-bourgeois with the bee’s tension aresupported her pessimism to become unsure of her own ability. Moreover, achronicle Gap Skin-Colors in America made people after she won theregional spelling bee. Thereof, Akeelah becomes more respectful and foundthe true meaning of life, all is full of love in all of sudden. Akeelah becomesmore open minded after her brutal and indecent. Hence, in this researchthe author will elaborate the logo therapy theory in a way to give a solutionfor status quo from the literary work analysis of ‘Akeelah and the Bee.Keywords: The logo-therapy theory, Status Quo, and Akeelah